ANÁLISE HISTOMORFOMÉTRICA DAS RESPOSTAS BIOLÓGICAS APÓS UTILIZAÇÃO DE HIDROXIAPATITA PURA (UEPG) E HIDROXIAPATITA COM COLÁGENO (UEPG), EM CONJUNTIVO SUBCUTÂNEO DE DORSO E EM DEFEITO CRÍTICO EM CALVÁRIA: ESTUDO EM RATOS - Goiris, Fabio Anibal Jara (2017)
The objective of this study was to evaluate in vivo two new biomaterials for bone substitution – pure hydroxyapatite and collagen hydroxyapatite – aiming at determining their biocompatibility in soft tissues and their ability to enable bone neoformation in critical size defects in rats’ calvaria. Both types of synthetic hydroxyapatite were developed by the Chemistry department of the State University of Ponta Grossa – Pure hydroxyapatite (HaP) and Hydroxyapatite with collagen (HCol). The third synthetic hydroxyapatite used as a comparing element was the commercial hydroxyapatite Alobone® (HaAl), which is available in the Brazilian market. Experiment 1 was carried out with the animals’ dorsal connective tissue and used 45 Wistar female rats, divided randomly into three groups of 15 animals each (HaP, HaCol and HaAl) which were euthanized after 7, 15 and 30 days of operation.The histomorphometric exam after 30 days revealed the absence of inflammatory cell characteristic infiltrates and the presence of non-inflammatory collagen fibers. These results show the biocompatibility of the material implanted. Experiment 2 used 60 Wistar rats divided randomly into 4 groups (Group 1, HaP; Group 2, HaCol; Group 3, HaAl and Group 4, Control). Critical size defects of 8mm were performed in the calvaria and the three biomaterials were implanted. All groups also received collagen membrane. On day 30, inflammatory response on the defect was practically absent in all groups, mainly when compared to the period of 7 days. Some areas of bone neoformation were seen. There was predominance of osteoblasts, osteocytes and macrophages in lower amount. Regarding the radiographic aspect, after 30 days our study confirmed a marked biodegradation of the hydroxyapatite and signs of bone neoformation. The histomorphometric results of the synthetic hydroxyapatite implant demonstrated the probable occurrence of intramembranous ossification from the granulation tissue with the presence of bone-resident macrophages. It was possible to conclude that the results of our study in vivo can be used as a preliminary source of information about biocompatibility, biodegradability and bone neoformation from the implant of new biomaterials in vivo.